Erythropoietic protoporphyria life impact and genetic health trajectory (LIGHT) study in Europe: a cross-sectional online questionnaire - Hetanshi Naik; Kristen Wheeden; Susan D. Mathias; Chelsea Norregaard; Adaeze Q. Amaefule; Melanie Chin; Manisha Balwani (Orphanet Journal of Rare Diseases, 2026)
Abstract Background Erythropoietic protoporphyria and X-linked protoporphyria (collectively, EPP) are rare inherited metabolic disorders of the heme biosynthetic pathway characterized by severe photosensitivity and painful phototoxic reactions upon sunlight exposure. This study sought to describe health-related quality of life, symptoms, and healthcare resource utilization in European patients with EPP. Participants aged ≥ 12 years with a diagnosis of EPP residing in France, Germany, Italy, Spain, or the UK completed a one-time online questionnaire. Patient consent and ethics approval were obtained. Results Ninety-one adults and 10 adolescents participated; 76% of adults and 38% of adolescents could spend ≤ 30 minutes in direct or indirect sunlight before prodromal symptoms started. Thirty-six percent (Italy) to 67% (Spain) of participants experienced prodromal symptoms ≥ 5 times in the past three months. Sixty-nine percent of participants experienced pain after < 30 minutes of direct sunlight, and over half experienced pain from indirect sunlight. The most recent phototoxic reaction limited daily activities “very much” in 58% of participants (range: 40% Spain to 86% UK). Participants reported a high emotional burden, including sadness/depression (66%), anxiety (60%), frustration (86%), loneliness (74%), and isolation (84%) due to their EPP. EPP negatively impacted work productivity for 9% (Italy) to 42% (France) of participants currently working. Conclusions Europeans with EPP frequently experience prodromal symptoms and phototoxic reactions that impose a negative impact on health-related quality of life and ability to do daily activities, highlighting the need for early diagnosis and effective treatments.